Good agricultural practices for ware potato production in Cameroon: Trainer guide - Harahagazwe, D.; Atieno, E.; Schulte-Geldermann, Elmar; Kromann, P.; Mafouo, H.; Anagho, R.; Schuffenhauer, A.; Sossou, L.; Breitenstein, A.; Festus, K.A. (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2018)
The Trainer Guide is the master document, it comprises three major parts: (i) the course overview, (ii) the four training modules also found in the Producer Manual, and (iii) the appendices. The course overview presents the training curriculum and all materials to be used. The second part of the guide consists of the training modules, alongside with trainer’s notes and instructions. In the last part (appendices), the Guide provides suggested questions and take home messages per theme as outlined in the Trainer Visual Aid.